UPAYA PENINGKATAN PENGETAHUAN PADA PELAJAR SMAN 1 BANTUL TENTANG PENCEGAHAN PENYALAHGUNAAN NARKOBA DENGAN INTERVENSI CBIA-NARKOBA - Sinta Rachmawati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2016)
AbstractBackground: Prevention programme of drug abuse in adolescents can be done in a schoolsetting. Evidence-based interventions is a must to guarantee the effectiveness of the methods.CBIA (Community Based Interactive Approach) is educational method based on interactiveapproach. It was proved to enhance health knowledge in community setting. CBIA-Drugs wasadopted from CBIA to improve knowledge of high school students to resist drugs.Objective: The objective of this study was to measure the effectiveness of CBIA-Drugs.Method: It was a quasi-experimental design with pretest-posttest control group design. Eachgroup of CBIA-Drugs and control consisted of 30 respondents. The relationship betweenvariables was analyzed by Wilcoxon Signed Rank and Mann Whitney, used 5% level ofconfidence.Result: The results of this study found that there were significant differences in pretest andposttest of knowledge on CBIA-Drugs group (p <0.05). It was concluded that knowledge wereimproved after intervention. CBIA-Drugs were able to maintain the consistency of theincreasing knowledge three weeks after the intervention. Keywords: Knowledge, CBIA, Drugs